Pengembangan Sistem Pelaporan Daerah Pasca Bencana Menggunakan WEBGIS (Studi Kasus Badan Penanggulangan Daerah Pasca Bencana Daerah, Kabupaten Ponorogo) - Estrisantya Irsyadi Azzahrah; Faizatul Amalia; Fatwa Ramdani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The potential for disasters in Ponorogo Regency is handled by the Badan Penanggulangan Bencana Daerah (BPBD). Recording of post-disaster reports at BPBD Ponorogo Regency is still done manually using Microsoft Excel and Microsoft Power Point for disaster publications to the public through the WhatsApp application. So we need a website-based system to facilitate reporting and publication of reports to the public as a form of data transparency. TRC (Quick Reaction Team) can record reports directly on the system. After being reviewed by PUSDALOPS and verified by the Kepala Pelaksana, the results of report verification can be accessed by the public via the website and using a GIS (Geographic Information System) to facilitate accurate reading of data by the public by directly looking at the affected areas on the map. This study uses the Waterfall method, data collection for needs analysis is carried out by interviewing one of the BPBD employees of Ponorogo Regency. The requirements analysis resulted in 23 functionalities which were implemented using the PHP programming language and the Laravel Framework, Leafleat js as a library for displaying maps, and the mySQL database. The implementation results tested using white-box, black-box testing, usability testing, Pearson product testing, split half testing and testing matrix model testing. From these tests, it was obtained valid results for white-box testing, one test was invalid from a total of 23 test-cases in black-box testing. For usability testing, a score of 62.5 was obtained or it was in the 'good' category. Meanwhile, for the feature validation test, there are 4 valid features, 6 invalid features and the rest cannot be calculated because there is a costant variable. The accuracy of GIS (Geographic Information System) using a test matrix model, the value is 80%.